(untitled) (Journal of the Bangladesh Agricultural University, 2011)
The experiment was carried out during the period from July 2008 to March, 2009 at the Biotechnology Laboratory, Department of Biotechnology, Bangladesh Agricultural University, Mymensingh. The present investigation was to be better source for shoot multiplication. The calli derived from leaf discs were cultured on shoot induction media containing different combinations and concentrations of BAP (1.0, 1.5, 3.0 and 6.0 mg/L) and Kn (0.5, 1.0, 1.5 and 2.0 mg/L). The highest percentage of shoot regeneration (91.66%) and the highest shoot length was 4.24 (cm) with a minimum number of days (13.33) was observed in the MS medium supplemented with 3.0 mg/L BAP and 0.5 mg/L Kn. Thus shoot multiplication in successive subculture was possible. The present investigation was carried out to study the in vitro shoot multiplication in gladiolus by using leaf disc as explants Keyword: Shoot proliferation; Micropropagation; BAP: 6-benzylamino purine; Kn: Kinetin; Leaf disc DOI: http://dx.doi.org/10.3329/jbau.v9i1.8739 JBAU 2011; 9(1): 21-26